1990
DOI: 10.1089/jop.1990.6.285
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Intraocular Pressure on Axial Elongation

Abstract: The role of intraocular pressure (IOP) on axial elongation was studied by the following three experiments. 1) Thickness of the sciera in the lid-sutured-myopia of three monkeys was examined by light microscopy. The sciera of the experimental eye in the posterior pole was thinner than that of the control eye, but no differences were found in the equatorial and limbal parts of the sciera.2) By increasing IOP, the scierai wall extensibility in 8 normal, enucleated rabbit eyes was measured by placing the foil stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0
1

Year Published

1993
1993
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 2 publications
0
13
0
1
Order By: Relevance
“…Various procedures such as raising the intraocular pressure in rabbits, or manipulation of the lens in the 3-week-old rabbit lead to an increase in axial length [Tokoro et al, 1990;Kugelberg et al, 1997]. Lens removal in the monkey and rabbit decreases axial growth [Wilson et al, 1987;Kugelberg et al, 1996].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various procedures such as raising the intraocular pressure in rabbits, or manipulation of the lens in the 3-week-old rabbit lead to an increase in axial length [Tokoro et al, 1990;Kugelberg et al, 1997]. Lens removal in the monkey and rabbit decreases axial growth [Wilson et al, 1987;Kugelberg et al, 1996].…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies in primates have demonstrated that inadequate visual input can significantly increase axial growth of the eye [Raviola and Wiesel, 1986]. Intraocular pressure may also influence axial length [Tokoro et al, 1990]. In the 3-week-old rabbit, both axial length and corneal diameter were significantly increased in eyes implanted with a thick silicone intraocular lens [Kugelberg et al, 1997].…”
Section: Introductionmentioning
confidence: 99%
“…In this connection, intraocular pressure (IOP) has been hypothesized to influence eye growth and perhaps to cause axial myopia (Pruett, 1988 ;Tokoro, Funata and Akazawa, 1990). However, experimental studies of such mechanisms have provided incon-clusive results (Wilkinson and Hodos, 1991 ;Nickla, Wildsoet and Wallman, 1998b ;Papastergiou et al, 1998a).…”
Section: Introductionmentioning
confidence: 99%
“…(Optom Vis Sci 2008;85:97-105) Key Words: intraocular pressure, myopic progression, axial length, children's vision T he idea that intraocular pressure (IOP) may play a role in myopia development has been in the literature for more than 140 years 1 and continues to receive attention in more recent times. [2][3][4] Studies that have compared the IOP in subjects with myopia to the IOP in non-myopic persons of similar age have provided differing results. Studies that have found a relationship between IOP and refractive error have reported an association in children, 4 -7 adults, 5,8 and presbyopic adults.…”
mentioning
confidence: 99%